2021
DOI: 10.3390/ijms22168429
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolic Modulatory Role of Naltrexone in BV-2 Microglia Cells

Abstract: Naltrexone is an opioid receptor antagonist commonly used to treat opioid and alcohol dependence. The use of low dose naltrexone (LDN) was found to have anti-inflammatory properties for treatment of diseases such as fibromyalgia, Crohn’s disease, multiple sclerosis and regional pain syndromes. Related to its anti-neuroinflammatory properties, the mechanism of action is possibly mediated via Toll-like receptor 4 antagonism, which is widely expressed on microglial cells. The aim of the present study was to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Low-dose Naltrexone (LDN) is commonly used off-label for people with ME/CFS, a condition characterized by debilitating fatigue and exertional intolerance that has significant clinical overlap with long COVID ( 78 ). From a mechanistic perspective, one model of LDN’s efficacy is through suppressive effects on microglia cells of the central nervous system and attenuation of proinflammatory cytokines ( 80 ). Microglia are resident macrophages in the brain and spinal cord and normally exist in a resting state but once activated produce proinflammatory factors that interact with neurons to cause hyperalgesia and “sickness response symptoms” such as fatigue, malaise, hypoactivity, sleep changes, etc., which have been demonstrated in animal models ( 80 , 81 ); there is intense interest in the role that these and other macrophage-derived cells might play in long COVID, particularly in neurocognitive symptoms ( 82 ).…”
Section: Current State Of Long Covid Management and Potential Therape...mentioning
confidence: 99%
See 1 more Smart Citation
“…Low-dose Naltrexone (LDN) is commonly used off-label for people with ME/CFS, a condition characterized by debilitating fatigue and exertional intolerance that has significant clinical overlap with long COVID ( 78 ). From a mechanistic perspective, one model of LDN’s efficacy is through suppressive effects on microglia cells of the central nervous system and attenuation of proinflammatory cytokines ( 80 ). Microglia are resident macrophages in the brain and spinal cord and normally exist in a resting state but once activated produce proinflammatory factors that interact with neurons to cause hyperalgesia and “sickness response symptoms” such as fatigue, malaise, hypoactivity, sleep changes, etc., which have been demonstrated in animal models ( 80 , 81 ); there is intense interest in the role that these and other macrophage-derived cells might play in long COVID, particularly in neurocognitive symptoms ( 82 ).…”
Section: Current State Of Long Covid Management and Potential Therape...mentioning
confidence: 99%
“…From a mechanistic perspective, one model of LDN’s efficacy is through suppressive effects on microglia cells of the central nervous system and attenuation of proinflammatory cytokines ( 80 ). Microglia are resident macrophages in the brain and spinal cord and normally exist in a resting state but once activated produce proinflammatory factors that interact with neurons to cause hyperalgesia and “sickness response symptoms” such as fatigue, malaise, hypoactivity, sleep changes, etc., which have been demonstrated in animal models ( 80 , 81 ); there is intense interest in the role that these and other macrophage-derived cells might play in long COVID, particularly in neurocognitive symptoms ( 82 ). Additionally, data suggest that the benefits of LDN treatment in ME/CFS are mediated by its regulatory role involving the Transient Receptor Potential Channel Melastatin 3 ( 83 ).…”
Section: Current State Of Long Covid Management and Potential Therape...mentioning
confidence: 99%
“…In this study, the inhibition of neuroinflammation by skimmianine was established following pre-treatment with the compound for 30 min, followed by stimulation with LPS for 24 h. However, a study reported by Kučić et al [ 39 ], showed that the inhibition of neuroinflammation was in fact possible by stimulating BV-2 microglia prior to treatment with low concentrations of naltrexone. It would therefore be interesting if future studies could determine whether reversing the sequence of skimmianine treatment and LPS stimulation would affect the anti-inflammatory activity of the compound.…”
Section: Discussionmentioning
confidence: 88%
“…Among them, Astemizole has been reported that immunosuppressive potential of Astemizole against T-cell proliferation and cytokine secretion in macrophages by modulating mitogen-activated protein kinase (MAPK) signaling pathway ( Jakhar et al, 2018 ). As a result of low-dose Naltrexone administration, BV-2 microglia cells acquired a quiescent anti-inflammatory M2 phenotype from highly activated pro-inflammatory phenotypes ( Kučić et al, 2021 ). Furthermore, low-dose naltrexone has been shown to modulate Toll-like receptor four signaling as well as transiently blockend endogenous opioid receptors to reduce glial inflammation ( Toljan and Vrooman, 2018 ).…”
Section: Discussionmentioning
confidence: 99%